Dose and time-dependent sub-chronic toxicity study of hydroethanolic leaf extract of Flabellaria paniculata Cav. (Malpighiaceae) in rodents - Akindele, Abidemi J.; Adeneye, Adejuwon A.; Salau, Oluwole S.; Sofidiya, Margaret O.; Benebo, Adokiye S. (Frontiers in Pharmacology, 2014)
Flabellaria paniculata Cav. (Malpighiaceae) is a climbing shrub, the preparations of which are used in the treatment of wounds and ulcers in Nigeria and Ghana. This study investigated the sub-chronic toxicity profile of the hydroethanolic leaf extract of Flabellaria paniculata (HLE-FP). HLE-FP was administered p.o. (20, 100 and 500 mg/kg) for 30 and 60 days to different groups of rats. Control animals received 10 ml/kg distilled water. In the group of animals for reversibility study, HLE-FP administration ceased on the 60th day and animals were monitored for a further 15 days. Results showed that oral treatment with HLE-FP for 30 days caused significant (p< 0.05) reductions in weight gain pattern compared to control. These changes were sustained with 60 days treatment. However, no significant (p>0.05) differences in relative organ weights between control and treatment groups were observed. HLE-FP-treated rats showed significant (p< 0.05) increases in Hb, PCV and RBC on day 30 and significant (p< 0.05) increases in MCV and MCH indices on day 60 compared to control. There were significant (p< 0.05) elevations in serum K+, urea and creatinine compared to control. The liver function tests showed slightly but non-significant alterations when compared to control. Biochemical findings were supported by histopathological observations of vital organs including the kidney and liver. Toxicities observed in respect of kidney function were irreversible at 15 days of stoppage of treatment. In the acute toxicity study, HLE-FP given p.o. caused no lethality at 5000 mg/kg but behavioural manifestations like restlessness, generalized body tremor, feed and water refusal were observed. The i.p. LD50 was estimated to be 2951.2 mg/kg. Findings in this study showed that HLE-FP is relatively non-toxic on acute exposure and generally safe on sub-chronic administration, but could be deleterious on the kidneys on prolonged oral exposure at a high dose. Thus, caution should be exercised with i